2018
DOI: 10.1017/s1355617718000747
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Mild Cognitive Impairment in Essential Tremor: How Many and Which Neuropsychological Tests?

Abstract: Objectives: Essential tremor (ET) confers an increased risk for developing both amnestic and non-amnestic mild cognitive impairment (MCI). Yet, the optimal measures for detecting mild cognitive changes in individuals with this movement disorder have not been established. We sought to identify the cognitive domains and specific motor-free neuropsychological tests that are most sensitive to mild deficits in cognition as defined by a Clinical Dementia Rating (CDR) of 0.5, which is generally associated with a clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…A 2017 cross sectional analysis of 128 older patients with essential tremor found that both amnestic and non-amnestic mild cognitive impairment (MCI) subtypes were represented (n=24); amnestic MCI, single and multi-domain, represented about 70% (n=17) of cases 68. Multi-domain amnestic MCI was the most common subtype (n=13; 54%) Five neuropsychological tests that are sensitive to mild cognitive deficits in patients with essential tremor (as defined by a Clinical Dementia Rating of 0.5) are the California Verbal Learning Test II Total Recall, Logical Memory II, Verbal-Paired Associates I, category Switching Fluency, and Color-Word Inhibition 69…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…A 2017 cross sectional analysis of 128 older patients with essential tremor found that both amnestic and non-amnestic mild cognitive impairment (MCI) subtypes were represented (n=24); amnestic MCI, single and multi-domain, represented about 70% (n=17) of cases 68. Multi-domain amnestic MCI was the most common subtype (n=13; 54%) Five neuropsychological tests that are sensitive to mild cognitive deficits in patients with essential tremor (as defined by a Clinical Dementia Rating of 0.5) are the California Verbal Learning Test II Total Recall, Logical Memory II, Verbal-Paired Associates I, category Switching Fluency, and Color-Word Inhibition 69…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Study Group et al, 2006b;Benito-León, Louis, Mitchell, & Bermejo-Pareja, 2011;Bermejo-Pareja et al, 2007;Cersonsky et al, 2018;Collins et al, 2017), depressive symptoms , personality changes (Thenganatt & Louis, 2012), changes in sleep patterns (Benito-León, Louis, & Bermejo-Pareja, 2013;Gerbin, Viner, & Louis, 2012), changes in visual reaction time (Jiménez-Jiménez et al, 2010), and hearing impairment Ondo, Sutton, Dat Vuong, Lai, & Jankovic, 2003).…”
Section: Louis Bermejo-pareja and Neurological Disorders In Central Smentioning
confidence: 99%
“…The current view of essential tremor (ET), one of the most common adult neurological disorders (Benito-León, 2009;Louis & Ferreira, 2010), is that it may be a family of diseases, unified by the presence of kinetic tremor, and characterized by etiological, clinical and pathological heterogeneity (Benito-León, 2014;Benito-León & Louis, 2006;. Aside from classic motor manifestations, ET is now considered a heterogeneous entity associated with a number of nonmotor manifestations, Sengul, Sengul, Sural, Bakim, & Forta, 2015) including cognitive disorders (Benito-León, Louis, Bermejo-Pareja, & Neurological Disorders in Central Spain Study Group, 2006a; Benito-León, Louis, Bermejo-Pareja, & Neurological Disorders in Central Spain Study Group et al, 2006b;Benito-León, Louis, Mitchell, & Bermejo-Pareja, 2011;Bermejo-Pareja et al, 2007;Cersonsky et al, 2018;Collins et al, 2017), depressive symptoms , personality changes (Thenganatt & Louis, 2012), changes in sleep patterns (Benito-León, Louis, & Bermejo-Pareja, 2013;Gerbin, Viner, & Louis, 2012), changes in visual reaction time (Jiménez-Jiménez et al, 2010), and hearing impairment Ondo, Sutton, Dat Vuong, Lai, & Jankovic, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The study, which began in July 2014, recruited participants through the International Essential Tremor Foundation (IETF) as well as other study websites. As described previously (31,32), participants who met the following eligibility criteria were recruited: (1) diagnosis of ET, (2) minimum age of 55 years, (3) no brain surgery for the treatment of ET, (4) willingness to participate in testing and enroll as a brain donor. All portions of the study were approved by the Yale University and Columbia University Internal Review Boards and all participants signed informed consent upon enrollment.…”
Section: Recruited Participantsmentioning
confidence: 99%
“…The neuropsychological evaluation at each assessment comprised a comprehensive in-person cognitive test battery in each participant's home, a telephone interview with an informant (a close family member or friend of the participant), and subjective written summaries from the trained research associates summarizing qualitative observations regarding cognitive and functional abilities for each participant. The cognitive test battery excluded tests whose scores relied on the accuracy of motor responses so as not to disadvantage participants with more severe tremor (31,32 (52), and WAIS Visual Puzzles subtest (50)]. Aggregate scores for each cognitive domain were calculated as an average of the z-scores for each test.…”
Section: Neuropsychological Evaluationmentioning
confidence: 99%